2017
DOI: 10.3389/fnins.2017.00147
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Listening Increases the Liking for Music Regardless of Its Complexity: Implications for the Appreciation and Aesthetics of Music

Abstract: Psychological and aesthetic theories predict that music is appreciated at optimal, peak levels of familiarity and complexity, and that appreciation of music exhibits an inverted U-shaped relationship with familiarity as well as complexity. Because increased familiarity conceivably leads to improved processing and less perceived complexity, we test whether there is an interaction between familiarity and complexity. Specifically, increased familiarity should render the music subjectively less complex, and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 82 publications
8
61
0
1
Order By: Relevance
“…Participants were not asked to prove their familiarity by writing down the song title or the band. We expect participants to be more motivated to entrain with a stimulus, if they have the impression to know the music (see also [ 82 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were not asked to prove their familiarity by writing down the song title or the band. We expect participants to be more motivated to entrain with a stimulus, if they have the impression to know the music (see also [ 82 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Stupacher et al [ 77 ], in their second study, investigated whether listeners’ groove ratings were influenced by their familiarity with the music, but did not observe such an influence either. Recently, Madison & Schiölde [ 82 ] found that repeated exposure to music (i.e. augmenting listeners’ familiarity with the music) also augmented listeners’ aesthetic appreciation of the music.…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say, a standard measure of the ‘success’ of a musical work is the music’s enticement to hear the work repeatedly. In fact, musical preference often develops over multiple hearings (Madison & Schiölde, 2017). While Madsen et al (2019) reported sustained ISC across repeated hearings of unfamiliar music, future research can take a more nuanced approach to investigate the interplay of engagement, preference, multiple hearings, degree of focus, and modes and contexts of listening.…”
Section: Discussionmentioning
confidence: 99%
“…乐偏好具有重要关联 [50,68,69] . Martindale 和Moore [68] 较早探讨了音乐文化经验在音乐偏好产生过程中的 作用机制, 提出了音乐偏好的"原型"假设(prototype hypothesis).…”
Section: 已有研究总体上认为 音乐文化经验与个体音unclassified